The second half of the 20th century in Chile: the crisis as a critical and regenerative phenomenon of modernity - Fuentes H., Pablo (Universidad de Chile. Facultad de Arquitectura y Urbanismo, 2008)
The fortunate promise of modernity maintained until the 50s in Chile, was seriously questioned during the 60s. Architectural debates that pointed out the flaws of the development of a needless social medium exposed the wide crisis of the system. The city and the architecture were revealed as examples of the crisis.